Revolutionizing Education: Unlocking the Potential of Asynchronous Video for Interactive Online Learning - Saluky; Nurul Bahiyah (Ilmu Inovasi Nusantara, 2023)
The traditional education landscape has witnessed a significant transformation in recent years due to advancements in technology and the growing demand for flexible learning options. Asynchronous video has emerged as a powerful tool in online education, offering learners the freedom to access course materials and engage with interactive content at their own pace and convenience. This paper explores the potential of asynchronous video in revolutionizing education by unlocking new possibilities for interactive online learning. The paper begins by discussing the limitations of traditional synchronous learning models and the need for innovative approaches that cater to the diverse learning styles and schedules of today's students. It then delves into the concept of asynchronous video, highlighting its key features and advantages. By enabling learners to access video lectures, tutorials, and demonstrations anytime and anywhere, the asynchronous video promotes self-paced learning and facilitates personalized educational experiences. Moreover, the paper examines how interactive elements can be seamlessly integrated into asynchronous video content. By incorporating quizzes, assessments, and interactive discussions within video platforms, educators can foster active engagement, promote critical thinking, and enhance knowledge retention. The potential of augmented reality (AR) and virtual reality (VR) technologies in creating immersive and interactive learning experiences through asynchronous video is also explored. Furthermore, the paper addresses the challenges and considerations associated with implementing asynchronous video in educational settings. It discusses issues related to video production, accessibility, and learner support, offering practical solutions and best practices to overcome these hurdles. The paper highlights successful case studies and initiatives that have effectively harnessed the potential of asynchronous video for interactive online learning. It presents evidence of improved learning outcomes, increased student engagement, and enhanced instructor-student interaction through the utilization of asynchronous video